OC-165 No increase in surgical complication in patients treated with rescue therapy for acute severe ulcerative colitis: data from the UK IBD audit. (28th May 2012) - Lynch, R W; Down, C; Roughton, M; Arnott, I D; ,
Abstract : Introduction: High dose steroids followed by colectomy if required remains the mainstay of treatment for active ulcerative colitis (UC). Recently we have seen the introduction of second-line medical therapies with the hope of avoiding the need for surgery when medical therapy fails. Using a cohort of 2981 and 3049 ulcerative colitis patients from the 2nd and 3rd rounds of the UK IBD audit we aim to assess whether the use of second-line medical therapies has an impact on the need for surgery and complication of surgery when needed. Methods: We audited 3049 patients with ulcerative colitis. Median age was 42; there were 1421 females and 1628 males. There were 495 elective admission for surgery and 2504 acute admissions of which 882 were considered to have severe disease. Of the 2504 acute admissions; 157 underwent surgery during their admission. 202 Sites audited a median of 18 UC patients per site that were admitted with IBD between 1 September 2009 and 31 August 2010. The results of this were compared against the results from the 2008 UK IBD audit which collected data on 2981 UC patients of which there were 863 with severe disease. Of the severe patients 163 patients underwent surgery. 209 sites audited a median of 17 UC patients per site that were admitted with IBD between 1 September 2007 and 31 August 2008. Results: There was no significant change in the operative rate among ASUC patients, 18.9% (163/863) in 2008 and 17.8% (157/882) in 2010 (p<0.6). Additionally there was no significant change in the mortality within the surgical populations 2.5% (4/163) in 2008 vs1.9% (3/157) in 2010 (p<0.96). There were significantly more patients proceeding to surgery following anti-TNFα therapy in 2010 10.82% (17/157) vs 3.7% (6/163) (p<0.008). Using the Travis criteria we also found that there were significantly less high risk surgical patients in 2010, 67.5% (106/157) compared to 83.4% (136/163) (p<0.002); this was also reflected in a significant reduction in the overall amount of high risk patients in the ASUC population. Post-operative complications are not statistically different between patients who did and did not receive rescue medical therapy 40.0% (26/65) vs 34.8% (32/92) (p<0.8). There was also no statistical difference in complications between rounds, 32.5% (53/163) in 2008 vs 36.9% (58/157) in 2010 (p<0.4). Conclusion: The surgical rate has remained the same over the two audit periods; however there has been a significant reduction in the proportion of high risk patients undergoing operations. This could in part be related to the increased use of second line medical therapies between the two audit rounds, with significantly more patients receiving anti-TNFα prior to surgery. The use of second line medical therapies did not increase the risk of surgery. Competing interests: None declared.